Pencatatan Akuntansi Dan Manajemen Laba Pada Perusahaan Di Indonesia Selama Pandemi Coronavirus (Covid-19) - Sarlina Sari (Journal of Economic, Bussines and Accounting (COSTING), 2021)
This research is a descriptive qualitative study that aims to explore the practice of accounting records adopted by business people and companies in Indonesia during the Coronavirus pandemic by comparing it with previous literature which has similar characteristics, namely past events that have an impact on unstable financial conditions. The data used in this study are secondary data, such as the results of previous studies, accounting lecturer dialogue forum press releases, Indonesian Accountants Association press releases, and several other online information sources. Overall, the discussion of this study shows that several accounting techniques can be used to reduce the negative impact of a pandemic on corporate financial reports. Some of the techniques companies can use during a pandemic include fair value accounting, income smoothing, loss avoidance, and big-bath earnings management. The results of the discussion in this study contribute to recent debates about the relevance of accounting to society. Although accounting - both as a discipline and practice - cannot be blamed for the negative effects of the pandemic on companies, it can be blamed as a social science for failing to assist in mitigating the negative effects of the pandemic on the financial performance of companies when managers are not allowed to exercise significant accounting wisdom. to mitigate the negative effects of the pandemic on their balance sheet. As the pandemic gets worse, more basic questions will be asked about the contribution of accounting to society, especially in reducing the negative impact of a crisis or pandemic on companies. Keywords: Fair Value Accounting, Income Smoothing, Loss Avoidance, and Big-Bath Earnings Management, Coronavirus (Covid 19)